(untitled) (Journal of the College of Basic Education, 2024)
The research objective: The effect of teaching the principles of international humanitarian law on the achievement of third-grade intermediate students in the social subject. The research group consisted of (30) students. The research used the following materials and tools: The research materials are a list of principles of international humanitarian law and choices of positions. The following results were reached: - There are statistically significant differences at the level of (0.01) between the average scores of the experimental group students in the pre- and post-applications of the attitudes test in favor of the post-application. The size of the effect is large, indicating the difference between the average scores of the pre- and post-applications of the attitudes test for the experimental group, in favor of the post-application.